Migration, Retention and Return Migration of Health Professionals; Comment on “Doctor Retention: A Cross-sectional Study of How Ireland Has Been Losing the Battle” - Latha S. Davda; David R. Radford; Jennifer E. Gallagher (International Journal of Health Policy and Management, 2021)
Medical education and training of health professionals are linked with their recruitment and retention. Practising as a competent health professional requires life-long continuous training and therefore training structures in health systems appear to influence doctors job satisfaction, their well-being and their intentions to remain in that health system. The commentary critiques aspects of the paper on doctors retention in Ireland, while drawing some parallels with the United Kingdom. There appears to be an emerging type of health professional migrants ‘education tourists’ who travel to other countries to obtain medical education creating new routes of migration and this presents new challenges to source and destination countries. The global shortage of doctors and other health professionals further exacerbates health inequalities as seen in the present pandemic and therefore the increased need for research into health professionals’ migration and their integration.